Exploratory study on green emission technology in automotive industry - Ismail, Nurul Izyan Nadhirah; Ahmad Zaidi, Mohamad Faizal (2017)
Emission is anything that's been released or discharged to the world such as car exhaust, burps, and radio broadcasts.The automotive industry plays a significant role and main functions in the vehicle system.The number of vehicles on the roads is increasing day by day due to increased living standards and population. The main objective of this study is to explores the relationship between performance expectancy (PE), effort expectancy (EE), social influence (SI), facilitating conditions (FC) towards behavior intention (BI) and use behavior (UB) using UTAUT and to analyze green emission technology acceptance level in the automotive industry. The data will be collected through a unified theory of acceptance and use of technology (UTAUT) questionnaire survey.The data obtained will be processed using program Statistic Package for Social Science (SPSS).This study pointed behavioral intention has the highest influence on the use behavior by 61%. This study has found that environmentally friendly vehicles are a necessity in the future as conventional vehicles that use ICE using hydrocarbon fuels and cause environmental pollution problems caused by a large number of vehicles on the road.